Precision Molecular Pathology of Hodgkin Lymphoma (Molecular Pathology Library,, 2018)
This text provides a comprehensive and up-to-date overview of Hodgkin lymphoma. The volume reviews every facet of the cancer in great detail, including pathology, pathobiology, molecular genetics, microenvironment, epidemiology, treatment, and new therapeutic advances. The specific role of the lymphoma microenvironment is addressed, and the relationship of Hodgkin lymphoma to related non-Hodgkin lymphomas is covered as well. Written by experts in the field, Precision Molecular Pathology of Hodgkin Lymphoma is a valuable resource for oncologists, surgeons, pathologists, clinical trainees, and investigators engaged in the diagnosis, treatment, and research studies of this lymphoid neoplasm. .